Odpowiedzi

  • Użytkownik Zadane
2010-03-15T20:10:21+01:00
A) 1-6/7x=4/7 /*7
7-6x=4
-6x=-3
x=2

b) x/6-1/6=1 /*6
x-1=6
x=7

c) 2/5(3-x)=-2 /*5
2(3-x)=-10
6-2x=-10
-2x=-16
x=8

d)3/4(2-3x)=-6 /*4
3(2-3x)=-24
6-9x=-24
-9x=-30
x=3⅓

e) 1/5(x-3)=9-x /*5
x-3=9-x
2x=12
x=6
1 5 1
Najlepsza Odpowiedź!
2010-03-15T20:10:48+01:00
A) 1-6/7x=4/7
-6/7x=4/7-1
-6/7x=-3/7
x=-3/7:-6/7
x=-3/7*-7/6
x=2
b) x/6-1/6=1 *6
x-1=6
x=6+1
x=7

c) 2/5(3-x)=-2
6/5-2/5x=-2
-2/5x=-2-6/5
-2/5x=-16/5
x=-16/5:-2/5
x=-16/5*-5/2
x=8

d)3/4(2-3x)=-6
3/2-9/4x=-6
-9/4x=-6-3/2
-9/4x=-15/2
x=-15/2:-9/4
x=-15/2*-4/9
x=30/9
x=3 i 3/9=3 i 1/3
e) 1/5(x-3)=9-x
1/5x-3/5+x=9
6/5x=9+3/5
6/5x=45/5+3/5
6/5x=48/5
x=48/5:6/5
x=48/5*5/6
x=8
pozdrawiam:)


3 3 3